Rola Zakładu Ubezpieczeń Społecznych w kształtowaniu postaw wobec idei ubezpieczenia społecznego - Ceglarska-Jóźwiak, Joanna (Annales. Etyka w Życiu Gospodarczym, 2019)
Social insurance is one of the social security techniques based on the principles of universality, compulsion, comprehensiveness and solidarity. The basis for the functioning of social insurance is the existence of a community of insured people – all those who earn a living through their own work. This community creates a contribution fund from which benefits are paid when certain social risks occur. The proper functioning of social insurance relies on the mutual trust of all involved entities and the sense of joint responsibility for contributions to the Social Insurance Fund and the distribution of the fund. In particular, it is important that the insured trust the insurance institution and that the trust of this institution be ensured. However, we should remember that other entities, such as employers and doctors, are also involved. A lack of a sense of community means that abusing the Social Insurance Fund (failing to make contributions or extorting benefits) is perceived in society as resourcefulness, not as an unethical, blameworthy action, that damages the community of insured people and, consequently, also those who abuse it. Therefore, the question arises, what actions should the Social Security Institution take to build trust in social insurance among society? How is it possible to create or strengthen the sense of community among the insured? The Social Insurance Institution consistently implements various activities to build society’s trust in social insurance and build a sense of community. In order to do this, the government must get more involved in insurance education, and the legislator should ensure legal stability and certainty.